Molecular Marker Analysis of Days to Flowering in Vegetable Soybean (Glycine max (L.) Merrill) - Pornpan Pooprompan; Sirikul Wasee; Theerayut Toojinda; Jun Abe; Sontichai Chanprame; Peerasak Srinives (Agriculture and Natural Resources, 2006)
Days to flowering (DTF) in vegetable soybean is an important reproductive character of agronomic interest. This trait is useful for developing vegetable soybean cultivars with desirable flowering date, and eventually harvesting date. The objective of this study was to identify simple sequence repeat (SSR) markers associating with quantitative trait loci (QTL) for DTF in recombinant inbred lines (RILs) derived from the cross between the vegetable soybean cultivar ‘AGS292’ and the grain soybean line (G8891xG7945-31-3-5-5) or ‘K3’ grown in two environments. The SSR allele size profiling of the parents were analyzed with 162 markers to identify their polymorphism. The analysis was assayed for linkage relationships of DTF in a sub-population of 92 RILs. Molecular marker analysis of 63 polymorphic SSR markers revealed that at least two major and nineteen minor QTL were involved in controlling DTF. The QTL near SSR markers (Satt132 and Satt431) in molecular linkage group (MLG) J had the greatest effect on DTF. These results suggested that the putative QTL for DTF might be populationspecific as indicated by different genomic region that control the same trait in different mapping populations. The QTL found in this study could facilitate vegetable soybean breeders in performing marker-assisted selection (MAS) as early as in the seedling stage to improve vegetable soybean cultivars with desirable flowering date.